Research Directions in Tumor Angiogenesis - Chai, Jianyuan (IntechOpen, 2013)
Angiogenesis is an extension process of the cardiovascular network within human body. It is usually triggered by the demand of oxygen and nutrients from the fast growing tissue and uncontrollably dividing cells, as seen during wound healing and tumor progression. This book focuses on tumor angiogenesis and includes 8 chapters written by highly experienced scholars from five different countries. It is the goal of this book to provide readers with an update on the molecular and cellular mechanisms of this biological process and hopefully to point out some new research directions for future therapeutic adventure.